Clinical immunology : principles and practice - Rich, Robert R; Fleisher, Thomas A (Mosby, 1996)
Baylor University, Houston, Texas. Comprehensive, authoritative two-volume reference on clinical immunology, emphasizing diagnosis and treatment of immunological diseases. Includes clinicallyrelevant basic science. AIDS receives four chapters. Halftone illustrations & color plates.
Keywords: imunita; alergologie a imunologie; Immunity; Immune System Diseases; nemoci imunitního systému; Immune System; imunitní systém